Rationality, Time, and Self - Pearson, Olley (F.O.C.H.) (Springer International Publishing, 2018)
This book provides a new argument for the tensed theory of time and emergentism about the self. This argument derives in part from theories which establish our nature as rational and emotional beings whose behavior is responsive to reasons which are facts. It is argued that there must be reasons, hence facts, that can only be captured by tensed and/or first-personal language if our behavior is to be by and large rational and appropriate. This establishes the tensed theory of time and emergentism or dualism about the self, given the physical body can plausibly be fully described non-first-personally. In the course of this discussion the book also clarifies and defends a notion of fact and responds to McTaggart's paradox and Wittgenstein's private language argument.